The Rise and Fall of Judicial Self-Government in Poland: On Judicial Reform Reversing Democratic Transition - Śledzińska-Simon, Anna (German law journal, 2018)
This article argues that the establishment of the National Council of the Judiciary in 1989 and the empowerment of the general assemblies of court judges gave rise to the idea of judicial self-government in Poland. This very idea of self-government, implying that judges hold important decision-making or veto powers on matters concerning the judiciary, was regarded as a precondition of the separation of powers and judicial independence, neither of which existed under Communist rule. However, the package of laws introduced in 2017 marks the end of judicial self-government as we know it. Not only did it undermine the independence of the National Council of the Judiciary by altering the mode of electing its judicial members, but it also concentrated the power over the judiciary in the hands of the executive branch, allowing for, inter alia, the exchange of key positions in court administration and the reconfiguration of the Supreme Court. This article examines the impact of this “reform” on such values as independence, accountability, and transparency. Investigating the role of judicial self-government in ensuring the principle of separation of powers and democracy, the article concludes with an assessment of the early consequences of the introduced changes for the Polish judiciary.